T-lineage blast crisis of chronic myelogenous leukemia: simple record of 4 cases (Medical Journal of Indonesia, 2005)
Blast crisis (BC) transformation in chronic myelogenous leukemia (CML) can involve each differentiation lineage of the hematopoietic system, i.e. granulocyte, monocyte, erythrocyte, megakaryocyte, and lymphocyte lineage. The lymphoid blast crisis (BC) leukemia cells usually belong to B-lineage, commonly having the phenotype of Pre-B stage of the B-lineage, in which cell-surface immunoglobulin (sIg) is not yet expressed. In contrast, T-lineage BC of CML is extremely rare. The objective of this study is to describe the fenotype, fusion transcript of bcr-abl, TdT, and cytoplasmic CD3 in T-lineage BC CML cases. Case report study. This report shows a simple summary of 4 cases of T-lineage BC of CML which have been collected in the phenotypic and genotypic analysis study for 17 years (1987-2004). In all cases, the chromosomal analysis revealed the presence of t(9;22)(q34;q11) at presentation. Cell surface analysis were done at diagnosis. Casesâ mononuclear cells stored as 10% DMSO were retrieved to be performed reverse transcription (RT) PCR BCR-ABL multiplex to demonstrate the presence of the fusion transcript of bcr-abl. RT-PCR was also performed for detecting the expression of cytoplasmic CD3Îµ and terminal deoxynucleotydil transferase (TdT). The results of cell surface antigen (CSA) at presentation showed that 1 case was CD7+, CD5-, and CD2-; 1 case CD7+, CD5+, and CD2-; and 2 cases CD7+, CD5+ and CD2+ indicating that all these T-lineage BC of CML cells show the phenotype of pre-(pro-) thymic stage phenotype. In the present study, two cases showed b2a2, one e1a2, and one negative bcr-abl transcript. The RT-PCR revealed the presence of CD3ε mRNA in all cases, and TdT mRNA in only one case. These results can constitute a basis for the future analysis of T-lineage BC of CML from now on. (Med J Indones 2005; 14: 184-9)